Analisis Daya Dukung Tata Air untuk Monitoring Kinerja Pengelolaan DAS Poleang, Sulawesi Tenggara - La Gandri; Hasbullah Syaf; Musram Abadi; Umar Ode Hasani; La Ode Kasno Arif; Albasri (Al-Ard: Jurnal Teknik Lingkungan, 2023)
The carrying capacity of water resources for various uses is highly dependent on the condition of the quality, quantity and continuity of water in a watershed. The lack of research conducted in the Poleang Watershed greatly limits information regarding the carrying capacity of the watershed. This study aims to determine the carrying capacity of the watershed based on water management indicators in the Poleang watershed. The method used in this study uses Minister of Forestry No. P.61/Menhut-II/2014 concerning monitoring and evaluation of watershed management with 5 parameters namely Flow Regime Coefficient, Annual Flow Coefficient, Sediment Load, Flood, and Water Use Index. The results showed that KRA in the Poleang watershed was in the category of KRA ≤ 20 with very low class, KAT was in the category of 0.2 < KAT ≤0.3 with low class, MS reached 97.25 tons/day so it was in the category of M> 20 with very high class, flooding occurs 1 time a year with high class, IPA reaches 1,299.9, so it is in the category of IPA ≤1,700 with very bad class. So that it can be concluded that the carrying capacity of the Poleang water system is included in the medium carrying capacity class